Brownian dynamics simulations of the interactions between lactate dehydrogenase (LDH) and G- or F-Actin. Part I: Muscle and heart homo-isoforms - Njabon, Eric N.; Patouossa, Issofa; Carlson, Kristine L.; Lowe, Stephen L.; Forlemu, Neville Y.; Thomasson, Kathryn A. (Scientific African, 2020)
Glycolytic enzymes may compartment in cells by binding to cytoskeletal structures. One potentially important step in compartmentation is the binding of the cytoskeletal protein F-actin by lactate dehydrogenase (LDH). Brownian dynamics (BD) simulations of LDH interacting with G- or F-actin provided first-encounter snapshots and relative binding free energies. Models of muscle (LDH-M4) and heart (LDH-H4) isoforms of lactate dehydrogenase for four species (rabbit, human, rat and pig) were examined. Strong electrostatic interactions were observed between both monomeric and polymerized actin for LDH-M4, but not LDH-H4. These electrostatic field potentials were examined in detail and explained the differences in complex formations between LDH-M4 and LDH-H4 with G- and F-actin. Complexes formed between LDH-M4 and G-actin involved residues found in the surface grooves between the A/D and B/C subunits. Several binding modes occurred between LDH-M4 and F-actin, the most frequent of which involved two subunits of actin interacting with two subunits of LDH-M4. LDH-M4 interactions with F-actin relied on 10 residues, nine of which were conserved between species. All of these residues except two were located in the positive grooves between A/D and B/C subunits, where the protein's electrostatic potential is enhanced by its quaternary structure. LDH-H4, however, does not show unique binding modes nor does it have a favorable relative binding free energy compared to LDH-M4. Thus, BD supports experimental findings [Ehmann, J. D.; Hultin, H. O. Arch. Biochem. Biophys.1973, 154, 471], that LDH-M4 binds actin, but LDH-H4 does not.